Risk factors for incident anemia of chronic diseases: A cohort study - Lee, Yun-Gyoo; Chang, Yoosoo; Kang, Jihoon; Koo, Dong-Hoe; Lee, Seung-Sei; Ryu, Seungho; Oh, Sukjoong (PloS one, 2019)
Anemia of chronic disease (ACD) refers to hypoproliferative anemia in the context of acute or chronic activation of the immune system. There is a paucity of prospective data addressing the risk factors for ACD development. An association between common chronic diseases and ACD was examined cross-sectionally and longitudinally. A cohort of 265,459 healthy participants without ACD at baseline were prospectively followed annually or biennially. During average follow-up period of 62 months, 4,906 participants developed ACD (incidence rate 3.58 per 1000 person-years). Multivariable-adjusted hazard ratio (HR) [95% confidence interval (CI)] for incident ACD comparing estimated glomerular filtration rate 30-60 and < 30 vs. ≥ 60 ml/min/1.73 m2 were 3.93 [3.18-4.85] and 39.11 [18.50-82.69]; HRs [95% CI] for ACD comparing prediabetes and diabetes vs. normal were 1.19 [1.12-1.27] and 2.46 [2.14-2.84], respectively. HRs [95% CI] for incident ACD comparing body-mass-index (BMI) of < 18.5, 23-24.9 and ≥ 25 vs. 18.5-22.9 kg/m2 were 0.89 [0.78-1.00], 0.89 [0.80-0.99] and 0.78 [0.66-0.91], respectively. HRs [95% CI] for incident ACD comparing prehypertension and hypertension vs. normal were 0.79 [0.73-0.86] and 1.10 [0.99-1.23], respectively. Metabolic syndrome, hypertension, chronic liver disease, and chronic obstructive pulmonary disease were not associated with incident ACD. The severity of chronic kidney disease and diabetic status were independently associated with an increased incidence of ACD, whereas prehypertension and an increasing BMI were significantly associated with decreased risk of ACD.